Spor bilimleri fakültesi öğrencilerinin Covid-19 salgın döneminde uygulanan uzaktan eğitime yönelik tutumlarının incelenmesi - Boulayoun, Yassin (My University, 2022)
11 Mart 2020 tarihinde Dünya Sağlık Örgütü (WHO) tarafından pandemi olarak ilan edildikten sonra, COVID-19 pandemisi dünya çapında dramatik bir şekilde insan yaşamında kayba yol açmış ve halk sağlığı, eğitim sistemleri ve iş dünyası için benzeri görülmemiş bir zorluk yaşanmıştır (WHO 2020). Bu çalışmada, Türkiye'deki üç farklı spor bilimleri fakültesi öğrencilerinin COVID-19 salgını döneminde uygulanan uzaktan eğitime yönelik tutumları incelenmiştir. Araştırma; Marmara Üniversitesi, Bolu Abant İzzet Baysal Üniversitesi ve Muğla Sıktı Koçman Üniversitesi Spor Bilimleri Fakülteleri’nde uygulanmıştır. Bu amaçla verilerin toplanmasında Rahim Arslan (2021) tarafından geliştirilmiş “Salgın Döneminde Uygulanan Uzaktan Eğitime Yönelik Tutum Ölçeği” kullanılmıştır. Ölçek google form platformu kullanılarak hazırlanmış ve hedeflenen öğrencilere ulaşılmıştır Toplanan verilerin analizinde SPSS 25 kullanılmıştır. Elde edilen verilerin analizinde, betimsel analiz istatistiksel yöntemleri kullanılmıştır. Araştırmanın; birinci faktörü (uzaktan eğitimde üniversitenin sunduğu imkanlardan memnuniyet), ikinci faktörü (uzaktan eğitimde öğretim üyelerine yönelik tutum), ücüncü faktörü (online sınavlara yönelik tutum), dördüncü faktörü (uzaktan eğitimde iletişim ve erişim) ve beşinci faktörü (uzaktan eğitim ve yüz yüze eğitimin kıyaslanması) doğrultusunda öğrencilerin uzaktan eğitime yönelik tutum düzeyleri tespit edilmiştir. Elde edilen bulgulara göre öğrencilerin çevrimiçi eğitime karşı memnuniyet düzeyi uzaktan eğitimde üniversitenin sunduğu imkanlardan memnuniyete göre (X=3,45) kararsızım cevabını verirken, öğretim üyelerine yönelik tutuma göre (X=3,82) katılıyorum cevabını, online sınavlara yönelik tutuma göre (X=2,95) kararsızım cevabını, uzaktan eğitimde iletişim ve erişime göre (X=3,56) kararsızım cevabını, uzaktan eğitim ve yüz yüze eğitimin kıyaslanmasına göre ise (X=3,53) kararsızım cevabını vermişlerdir. Üniversiteler arasında karşılaştırma yaparken, üniversitenin sunduğu imkanlardan memnuniyet faktörüne göre (F= 13,508 p<0,05) Marmara Üniversitesi, Muğla Sıtkı Koçman Üniversitesi ve Bolu Abant İzzet Baysal Üniversitesi arasında anlamlı fark bulunmuştur. Dolayısıyla Marmara Üniversitesi öğrencileri Muğla SK ve Bolu AİB üniversitesi öğrencilerine göre daha olumsuz bir tutum içindeler. Öğretim üyelerine yönelik tutum faktörüne göre (F=5,880 p<0,05) Marmara Üniversitesi, Muğla Sıtkı Koçman Üniversitesi ve v Bolu Abant İzzet Baysal Üniverstesi arasında anlamlı fark bulunmuştur. Dolayısıyla Marmara Üniversitesi öğrencileri Muğla SK ve Bolu AİB üniversitesi öğrencilerine göre daha olumsuz bir tutum içindeler. Online sınavlara yönelik tutum faktörüne göre (F=3,118 p>0,05) üniversiteler arasında anlamlı bir fark bulunmamıştır. Dolayısıyla öğrencilerin tutumları kararsız şeklindedir. İletişim ve erişim faktörüne göre (F=11,099 p<0,05) Marmara Üniversitesi ve Muğla Sıtkı Koçman Üniverstesi arasında anlamlı bir fark bulunmuştur. Dolayısıyla Marmara Üniversitesi öğrencileri Muğla SK Üniversitesi öğrencilerine göre daha olumsuz bir tutum içindeler. Uzaktan eğitim ve yüz yüze eğitim faktörüne göre (F=0,274 p>0,05) üniversiteler arasında anlamlı bir fark bulunmamıştır. Cinsiyete göre tüm öğrencilerin karşılaştırmasını yaptığımızda uzaktan eğitimde üniversitenin sunduğu imkanlardan memnuniyet faktörüne göre kadın-erkek arasında anlamlı bir fark bulunmamıştır (p>0,05). Öğretim üyelerine yönelik tutum faktörüne göre kadın-erkek arasında anlamlı bir fark bulunmamıştır (p>0,05). Online sınavlara yönelik tutum faktörüne göre kadın-erkek arasında anlamlı bir fark bulunmuştur (p<0,05). Erkekler kadınlara göre daha olumlu bir tutum içindedirler. İletişim ve erişim faktörüne göre kadın-erkek arasında anlamlı bir fark bulunmuştur (p<0,05). Erkekler kadınlara göre daha olumlu bir tutum içindeler. Uzaktan eğitim ve yüz yüze eğitim faktörüne göre kadın-erkek arasında anlamlı bir fark bulunmuştur (p<0,05). Kadınlar erkeklere göre daha olumlu bir tutum içindeler. Genel olarak bakıldığında öğrencilerin online sınavlara yönelik tutumlarında ve üniversitelerin sunduğu imkanlardan memnuniyet açısından kararsızım, yani orta düzeyde memnuniyet içinde oldukları, ancak öğretim üyelerine yönelik düşüncede eğitimde iletişim ve erişimde ulaşabilme ve yüz yüze eğitime yönelik öğrencilerin daha olumluya (katılıyorum) yakın düşünce içinde oldukları bulunmuştur. Uzaktan eğitime yönelik tutumlarında üniversiteler arasında anlamlı bir fark olduğu görülmüştür ve cinseyete göre de genel olarak erkekler (X=3.49) kadınlara göre (X=3.43) daha olumlu düşünce

After being declared as a pandemic by the World Health Organization (WHO) on 11 March 2020, the COVID-19 pandemic has led to a dramatic loss of human life worldwide and presents an unprecedented challenge to public health, education systems and the world of work (WHO 2020). The social and education disruption caused by the pandemic is devastating: high rates of poverty and unemployment, deterioration of education’s levels due to disturbances related to some adaptations problems to the new reality of the imposed quarantine (bbc dünya haberler 2020). The COVID-19 hit the universities hard all around the world. On March 16, the universities in Turkey suspended face-to-face teaching and education was rapidly replaced by digital online formats (UZEM 2020). For a while the online education seems that it can replace the face-to-face education. However it soon it started to show lot of problems on different dimensions whether for teachers or students, the thing that reflected on the quality of education negatively (Telli Yamamoto, G. ve Altun, D. 2020). In this study we investigated about the attitudes of several sports sciences faculties students in Turkey towards distance education during the COVID-19 epidemic. The study has been applied on students of physical education and sports teaching, sports coaching and sports management deparments of Maramara University, Bolu Abant Izzet Baysal University and Muğla Sıtkı Koçman University. For this purpose we have used a valid and reliable scale “Developıng An Attıtude Scale Towards Dıstance Educatıon Applıed In The Perıod Of The Outbreak” developed by Rahim Arslan (2021) to collect the data. The scale was prepared using “google form” platform and sent to the targeted students by email and whatsapp. SPSS 25 program was used to analyse the collected data. Descriptive analysis and statistical methods were used in the analysis of the data obtained. The students' attitude levels towards distance education were determined based on the next five factors: the first factor of the research is “Satisfaction with the Facilities Provided by the University in Distance Education”, the second factor “Attitude towards Faculty Members in Distance Education”, the third factor “Attitude towards online exams”, the fourth factor “Communication and access in distance education” and the fifth factor “Distance education and face-to-face education”. According to the findings, the satisfaction level of the students towards online education and their satisfaction with the facilities offered by the university in distance education is as undecided, (X=3,45). According the attitude towards faculty members in distance education the students satisfaction is undecided (X=3,82). According the attitude towards online exams the students satisfaction is found again as undecided (X=2,95). According the communication and access in vii distance education the students satisfaction is found as undecided (X=3,56). According the comparison between distance education and face to face education findings the students satisfaction is found as undecided (X=3,53). When we compared between universities, according the facilities offered by the university in distance education satisfaction (F= 13,508 p<0,05), the results shown that there is a different between Marmara university, Muğla Sıtkı Koçman university and Bolu Abant İzzet Baysal University. According the attitude towards faculty members in distance education (F=5,880 p<0,05), the results shown that there is a different between Marmara University, Muğla Sıtkı Koçman University and Bolu Abant İzzet Baysal University. According the attitude towards online exams (F=3,118 p>0,05) the results shown that there is a different between all the universities. According the communication and access in distance education (F=11,099 p<0,05) the results shown that there is a different between Marmara University and Muğla Sıtkı Koçman University. According the comparison between distance education and face to face education (F=0,274 p>0,05) the results shown that there is no different between the universities. When we compared between the genders, according the facilities offered by the university in distance education satisfaction, the results shown that there is no significant different between males and females (p>0,05). According the attitude towards faculty members in distance education, the results shown that there is no significant different between males and females (p>0,05). According the attitude towards online exams, the results shown that there is a significant different between males and females (p<0,05). According the communication and access in distance education, the results shown that there is a significant different between males and females (p<0,05). According the comparison between distance education and face to face education, the results shown that there is a significant different between males and females (p<0,05). When we look at the results in general, the students were undecided in terms of attitudes towards online exams and their satisfaction with the opportunities offered by universities, that so we found that they have a moderately negative attitude, but according to the thoughts towards faculty members, communication and access in education, and positive thinking about face-to-face education, the students have more positive thoughts. Also it has been observed that there is a significant difference between universities students in their attitudes towards distance education, however according to the gender, it was found that male students (X=3.49) were more positive than female students (X=3.43).
Investigation on student’s attitudes of sports sciences faculty towards distance education during Covid-19 epidemic period
Keywords: COVID-19 (Disease); COVID-19 (Hastalık); Covid-19; çevrimiçi eğitim; Distance education; online education; Öğrenciler; Öğrenim ve öğretim; Spor; spor bilimleri fakültesi; Sports; sports science faculty; Students; Study and teaching; Uzaktan eğitim